Reuse Of Pacemakers In Ghana And Nigeria: Medical, Legal, Cultural And Ethical Perspectives. Issue 3 (11th April 2014) - Ochasi, Aloysius; Clark, Peter
Abstract: According to the World Health Organization (WHO) cardiovascular disease (CVD) is the leading cause of death globally. Over 80% of CVD deaths take place in low‐ and middle‐income countries (LMICs). It is estimated that 1 million to 2 million people worldwide die each year due to lack of access to an implantable cardiac defibrillator (ICD) or a pacemaker. Despite the medical, legal, cultural and ethical controversies surrounding the pacemaker reutilization, studies done so far on the reuse of postmortem pacemakers show it to be safe and effective with an infection rate of 1.97% and device malfunction rate of 0.68%. Pacemaker reutilization can be effectively and safely done and does not pose significant additional risk to the recipient. Heart patients with reused pacemakers have an improved quality of life compared to those without pacemakers. The thesis of this paper is that pacemaker reutilization is a life‐saving initiative in LMICs of Nigeria and Ghana. It is cost effective; consistent with the principles of beneficence, nonmaleficence, and justice with a commitment to stewardship of resources and the Common Good. Used pacemakers with adequate battery life can be properly sterilized for use by patients in LMICs who cannot afford the cost of a new pacemaker.